The Implementation of Economic Order Quantity for Raw Material Planning in SME Producing Terasi Crackers - Utami, R; Khadafi, S (IPTEK Journal of Proceedings Series, 2018)
Raw material planning in SME producing crackers is an essential matter since most of its raw materials do not last long and to avoid raw materials shortage or buildup stored in the warehouse. Therefore, the researchers offered a solution by implementing Economic Order Quantity (EOQ) method. From this research, it was concluded that the economic supply of raw materials (wheat flour) is 27.71 Kg with 14-day interval between orders, 6-day waiting time until the products are delivered, 16.47 Kg reorder point, 4.42 Kg safety stock value, and IDR 1,801,064 TIC.